Quadrinhos, Pintura e Literatura - Paula, Marcus Vinicius de (9 Arte (São Paulo), 2018)
The article is based on a comparison between Karl Bryullov’s The Last Day of Pompeii, 1833, and the comic book The Last Days of Pompeii, published by the comic book Edição Maravilhosa in the 1959, in order to identify affinities between this medium and the academic pictorial tradition. Specifically, intends to investigate how painting and comics interact with literary texts. The purpose is to verify if the inefficiency of the strategy of legitimating comics through literature has deeper roots.